Inter-individual Variation in Pain Sensitivity among Healthy Young Indian Adults- a pilot study - Aparna Rao, C; Savitha, D (Kathmandu University Medical Journal, 2023)
Background Pain perception, with inter-individual variability, is a challenge for both patients and clinicians. Distribution of pain sensitivity parameters being less explored in Indian population can vary with reports from outside India.Objective To describe distribution of pain sensitivity parameters using cold pressor test in healthy adults and to explore relationship of pain sensitivity with gender, vascular reactivity and parental history of hypertension.Method Pain was induced with non-dominant hand immersed in cold water (30C to 50C) in 150 subjects (75 males and 75 females) selected as per inclusion and exclusion criteria. Pain sensitivity (pain threshold, tolerance and unpleasantness), vascular reactivity (Δ change in blood pressure and pulse rate) were measured.Result Subjects demonstrated pain threshold [17.6 s (10.7, 26.6)], tolerance [40.2 s (30.0, 59.2)] and unpleasantness [7.0 (6.1,8.0)]. Pain unpleasantness showed a weak negative correlation with pain threshold and tolerance (p < 0.001). Pain threshold had moderate positive correlation with tolerance (p < 0.001). Males had significantly higher pain threshold and tolerance than females (p=0.004). Significant rise in post-test systolic and diastolic blood pressure (p < 0.001), decrease in pulse rate (p=0.007) were found compared to resting values. Pain tolerance showed a weak positive correlation with Δ systolic blood pressure (p=0.039). Subjects with positive parental history of hypertension showed higher pain unpleasantness scores (p=0.02).Conclusion The study demonstrated a wide range of pain sensitivity for narrow age and body mass index. Gender difference was observed for pain threshold and tolerance. Vascular reactivity was demonstrated. Subjective pain perception was higher in subjects with parental history of hypertension.